(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article discusses the priority directions for the development of small businesses in Uzbekistan, emphasizing the importance of free market mechanisms, competition, and private property protection in economic reforms. It highlights the role of small businesses in the country’s GDP, noting fluctuations in their share due to the growth of large enterprises. The article outlines key measures for enhancing the business environment, including improving regulatory frameworks, ensuring financial support, and strengthening market infrastructure. Additionally, it underscores the significance of effective small business management, emphasizing modern tools such as cloud collaboration systems. The study concludes that adhering to organizational principles and adapting management strategies are crucial for sustainable business growth and economic development.